Microarray analysis reveals ONC201 mediated differential mechanisms of CHOP gene regulation in metastatic and nonmetastatic colorectal cancer cells - Ashraf Al Madhoun (Nature Portfolio, 2021)
Abstract The imipramine ONC201 has antiproliferative effects in several cancer cell types and activates integrated stress response pathway associated with the induction of Damage Inducible Transcript 3 (DDIT3, also known as C/EBP homologous protein or CHOP). We investigated the signaling pathways through which ONC201/CHOP crosstalk is regulated in ONC201-treated nonmetastatic and metastatic cancer cell lines (Dukes' type B colorectal adenocarcinoma nonmetastatic SW480 and metastatic LS-174T cells, respectively). Cell proliferation and apoptosis were evaluated by MTT assays and flow cytometry, gene expression was assessed by Affymetrix microarray, signaling pathway perturbations were assessed in silico, and key regulatory proteins were validated by Western blotting. Unlike LS-174T cells, SW480 cells were resistant to ONC201 treatment; Gene Ontology analysis of differentially expressed genes showed that cellular responsiveness to ONC201 treatment also differed substantially. In both ONC201-treated cell lines, CHOP expression was upregulated; however, its upstream regulatory mechanisms were perturbed. Although, PERK, ATF6 and IRE1 ER-stress pathways upregulated CHOP in both cell types, the Bak/Bax pathway regulated CHOP only LS-174T cells. Additionally, CHOP RNA splicing profiles varied between cell lines; these were further modified by ONC201 treatment. In conclusion, we delineated the signaling mechanisms by which CHOP expression is regulated in ONC201-treated non-metastatic and metastatic colorectal cell lines. The observed differences could be related to cellular plasticity and metabolic reprogramming, nevertheless, detailed mechanistic studies are required for further validations.